The Main Character's Hierarchy of Needs in Itaewon Class - Weny Ayu Amelia; Yulis Setyowati; Ari Astutik (EL2J (English Language and Literature Journal), 2024)
This research aims to analyze hierarchy of needs using Abraham Maslow's theories on Korean Drama Itaewon Class (2020). This research is motivated by the existence of aspects of human needs which are reflected through the characters in the drama. This study aims to describe the process of fulfilling the levels of the hierarchy of needs carried out by main characters there are Park Saeroy and Jo Yiseo in Drama Itaewon Class. In conducting this research, the method is used descriptive qualitative method. The formulation of the problem in this study is what is the hierarchy of needs portrayed by the main characters in the drama Itaewon Class. This study uses the motivational theory of the hierarchy of needs by Abraham Maslow. Based on the study and discussion of research results, it can be concluded in the following paragraphs. The hierarchy of needs in the two main characters are (1) physiological needs, (2) safety and security needs, (3) belonging and love needs, (4) self-esteem needs, and (5) need for realization or self-actualization. Of the five levels of needs that exist, the two main characters have succeeded in fulfilling their needs up to the level of self-actualization.